Numerical Study of RC Beams Strengthened with Fe-Based Shape Memory Alloy Strips Using the NSM Method - Yeong-Mo Yeon; Ki-Nam Hong; Sugyu Lee; Sang-Won Ji (Applied Sciences, 2021)
This paper presents a finite element (FE) analysis for predicting the flexural behavior of reinforced concrete (RC) beams strengthened with Fe-based shape memory alloy (Fe-SMA) strips using a near surface mounted (NSM) method. Experimental results reported in the literature were used to verify the proposed FE model. FE analyses were conducted using OpenSees, a general-purpose structural FE analysis program. The RC beam specimens were modeled using a nonlinear beam-column element and a fiber element. The Concrete 02 model, Steel 01 model, and Pinching 04 model were applied to the concrete, steel reinforcement, and Fe-SMA strip in the fiber element, respectively, and the FE analysis was carried out in a displacement control method based on the Newton-Raphson method. The FE model of this study accurately predicted the initial crack load, yield load, and ultimate load. From parametric analyses, it was concluded that an increase in the compressive strength of the concrete increases the ductility of the specimen, and an increase in the level of recovery stress on the Fe-SMA strip increases the initial stiffness of the specimen.